PERAN ORANG TUA DALAM IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) UNTUK MENUMBUHKAN KARAKTER TANGGUNG JAWAB SISWA DI MI Al-MA’ARIF WRINGINSARI - Lia, Aulia Rahmawati; Rizqiyah Ratu Balqis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The lack of parental role in the implementation project of strengthening the Pancasila student profile and character building is still a problem that must be overcome. This study reveals the role of parents in the implementation project of strengthening the Pancasila student profile to foster students' responsible character at MI Al-Ma’arif Wringinsari. Namely the aim is to determine the role of parents in the implementation of the Pancasila Student Profile Strengthening Project (P5) in the success of the learning process at home. By using a Qualitative approach of the phenomenological type involving observation, interviews, and documentation. The results of the study indicate that 1.) The implementation of the Pancasila Student Profile Strengthening Project (P5) was carried out structurally and in collaboration with parents. 2.) the role of parents as the main educators at home in the formation of student character. 3) After the implementation of the Pancasila student profile strengthening project, it had a positive and sustainable impact.